Perceptions of Marketing & Digital Transformationin Greek Public Higher Education Organizations in the Context of Digital Darwinism - Nektarios Makrydakis (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Objective: Marketing and digital transformation in the public institutions of higher education in Greece, have key role in the context of the digital revolution. The study aimed at investigating the perceptions and views explicitly or implicitly of the management of Greek public universities regarding the need to adopt new practices such as marketing and its digital transformation and to find out the factors that shape perceptions. Research Design & Methods: The study adopted a quantitative method conducting in-depth interviews with rectors and vice-rectors of 10 representative Greek Universities. Findings: Results indicated that administrators believe that marketing and its digital transformation have great impact in attracting students and that the duration of the operating time of a university is directly related to the formation of perceptions about marketing and digital transformation in the context of Digital Darwinism. Implications & Recommendations: Universities will be able to understand the extent of their reaction to the adoption of new applications such as marketing. Contribution & Value Added: The present study is primarily a useful tool for public university administrations in their efforts to adopt marketing practices to understand which areas to focus on in order to effectively implement marketing and its digital transformation. The study also provides them with the tools to easily recognize their degree of maturity in terms of their culture and perceptions towards the application of marketing practices. In addition the study enriches the literature on the management field of higher education institutions. It highlights factors such as the duration of operation, the geographical location and the size of a university compared to administrative practices.